2010
DOI: 10.1029/2010gl043494
|View full text |Cite
|
Sign up to set email alerts
|

Lightning mapping observation of a terrestrial gamma‐ray flash

Abstract: [1] We report the observation with the North Alabama Lightning Mapping Array (LMA) related to a terrestrial gamma-ray flash (TGF) detected by RHESSI on 26 July 2008. The LMA data explicitly show the TGF was produced during the initial development of a compact intracloud (IC) lightning flash between a negative charge region centered at about 8.5 km above sea level (−22°C temperature level) a higher positive region centered at 13 km, both confined to the convective core of an isolated storm in close proximity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
181
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(210 citation statements)
references
References 28 publications
22
181
0
7
Order By: Relevance
“…The total charges were ±36.5 C in the two regions. This configuration is consistent with the altitude range of +IC lightning associated with TGFs [ Stanley et al , 2006; Shao et al , 2010; Lu et al , 2010]. In addition, a small uniform field (1.0 × 10 4 V/m × n ), pointed downward, was added to insure that the vertical component of the field did not become too small in the particle simulation volume.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The total charges were ±36.5 C in the two regions. This configuration is consistent with the altitude range of +IC lightning associated with TGFs [ Stanley et al , 2006; Shao et al , 2010; Lu et al , 2010]. In addition, a small uniform field (1.0 × 10 4 V/m × n ), pointed downward, was added to insure that the vertical component of the field did not become too small in the particle simulation volume.…”
Section: Resultsmentioning
confidence: 72%
“…Early sferics observations suggested that TGFs were associated with lightning, which at the time was interpreted +CG lightning associated with sprites [ Inan et al , 1996]. Currently, most TGFs are believed to be produced inside thunderclouds during the initial stage of upward positive intracloud (IC) lightning [ Stanley et al , 2006; Lu et al , 2010; Shao et al , 2010; Connaughton et al , 2010; Lu et al , 2011]. However, how the lightning is related to the TGF production has not been clear, nor has it been well understood why some lightning produces TGFs while many others do not [ Splitt et al , 2010; Smith et al , 2011].…”
Section: Introductionmentioning
confidence: 99%
“…These include: the intensity distribution of TGFs and their lower limit of intensity or threshold of occurrence, if any; the altitude range of the origin of the emission; the cutoff energy, variations of TGF spectra at the source; the beaming characteristics of the radiation; the type(s) of lightning that are associated with the production of TGFs, and the temporal relationships of TGFs to the lightning associated with them. The latter was first examined by Inan et al [1996] and more recently in papers by Cummer et al [2005], Stanley et al [2006], Lu et al [2010], Cohen et al [2010], Briggs et al [2010], and Connaughton et al [2010].…”
Section: Introductionmentioning
confidence: 99%
“…They usually occur in powerful thunderstorms, and have been associated mostly with intra-cloud discharges at altitudes in the range of 10-20 km (e.g. Lu et al, 2010). The TGF geographical distribution, for the most favorable detection conditions occurring in tropical regions , closely follows the lightning distribution (e.g.…”
Section: Introductionmentioning
confidence: 99%